Forensic accounting and its effectiveness on achieving the economic dimension of sustainable development - Fadhil Khudair , Jassim; Adnan Noman , Suaad (Journal of Economics and Administrative Sciences, 2024)
The research aims to clarify the concepts of Forensic accounting and the economic dimension of sustainable development and to explain the relationship that links them, and The research starts from a basic problem: the extent to which Forensic accounting contributes to achieving the economic dimension of sustainable development, To achieve the goal of the research, the researchers created a questionnaire consisting of two parts to test the two research hypotheses, The research sample consisted of (112) individuals working (academics and professionals) in the Federal Bureau of Financial Supervision and its affiliated bodies in Baghdad, and the researchers reached a set of Results , one of the important: That Forensic accounting has a positive and moral impact on the economic dimension of sustainable development, that the application of Forensic accounting in the local environment contributes to the efficiency and effectiveness of the professional performance of economic units, contributes to the preservation of public funds, and drives economic development, leading to the economic dimension of sustainable development.. Research Type: Research paper